الصورة في الكتاب المدرسي ودورها في التحصيل الدراسي على التلاميذ كتاب اللغة العربية سنة أولى ابتدائي نموذجا - - خولة لعمارة (جامعة محمد بوضياف بالمسيلة, 2025)
تهدف هذه الدراسة إلى تسليط الضوء على الصورة في الكتاب المدرسي ودورها في التحصيل الدراسي لدى التلاميذ في الطور الابتدائي انطلقت الدراسة من فرضية مفادها أن الصورة تلعب دورا فعالا في التحصيل الدراسي للتلاميذ كما أن جودة الصورة وتصميمها يؤثران بشكل مباشر على فهم التلاميذ لمحتوى التعليمي اعتمدت الدراسة على المنهج الوصفي التحليلي بالإضافة إلى أدوات ميدانية كالاستبيان و المقابلة من أجل رصد دور الصورة في تسهيل الفهم و الإستعياب بالإضافة إلى أهمية الصورة في الكتاب المدرسي. أظهرت نتائج الدراسة أن الصورة تساعد على تبسيط المفاهيم وتسهم في جذب انتباه التلاميذ ولها دور فعال على عملية التحصيل كما تبين وجود بعض النقائص في نوعية الصور في الكتب المدرسية سواءا من حيث الجودة أو الإرتباط بالبيئة المحلية مما يستدعي إعادة النظر في طريقة التصميم في ضوء هذه نتائج قدمت الدراسة مجموعة من التوصيات ابرزها ضرورة تحسين نوعية الصور التعليمية وتكوين المعلمين على كيفية توظيفها بما يتماشى مع احتياجات التلاميذ. This study aims to shed light on the role of images in school textbooks and their impact on the academic achievement of primary school pupils. The study is based on the hypothesis that images play an active role in enhancing students' learning and that the quality and design of these images directly influence their understanding of educational content. The research adopted a descriptive-analytical approach, using field tools such as questionnaires and interviews to examine how images contribute to simplifying concepts and improving comprehension, as well as to highlight the overall importance of visuals in textbooks. The findings revealed that images help simplify complex ideas, attract students’ attention, and play an effective role in the learning process. However, the study also noted several shortcomings in the quality of images used in school textbooks, particularly in terms of visual clarity and their relevance to the students' local environment. This highlights the need to reconsider how these images are designed and integrated. In light of these results, the study presented a set of recommendations, most notably the need to improve the quality of educational images and to train teachers on how to use them effectively in line with students' needs and learning levels